Case Report: A Novel TNFAIP3 Mutation Causing Haploinsufficiency of A20 With a Lupus-Like Phenotype - Shaheen, Zachary R.; Williams, Sarah J. A.; Binstadt, Bryce A. (Frontiers in Immunology, 2021)
Genetic mutations that result in loss-of-function of the protein A20 result in an early-onset autoinflammatory disease – haploinsufficiency of A20 (HA20). The reported clinical presentations of HA20 include a Behcet’s disease-like phenotype and a more lupus-like phenotype. We have identified a novel mutation in the gene encoding A20 in a pediatric patient with chronic lymphadenopathy, lupus-like symptoms, and progressive hypogammaglobulinemia. This case illustrates the wide range of clinical symptoms, including immunodeficiency, that can occur in patients with HA20.